Menetapkan Pilihan Nilai Jual Obyek Pajak Bumi dan Bangungan sebagai Dasar Penghitungan Bea Perolehan Hak atas Tanah dan Bangunan - R. Murjiyanto; Samun Ismaya (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Fee for Acquisition of Land and Building (BPHTB) is an obligatory fee that must be paid by any parties receiving rights over land and building. In order to get certainty in paying BPHTB, it is necessary to change the values used as the standard in calculating BPHTB. This research discusses: first, what is the difference of transaction value gap with (NJOP PBB) in SPPT PBB? Second, what values that can be selected to be used as the standard of calculating BPHTB? This research was conducted using normative method supported by primary data. The findings conclude that: first, transaction values are generally higher than NJOP PBB written in SPPT PBB. Second, in order to gain certainty in the payment of BPHTB, it is necessary to set a reasonable value in NJOP PBB as written in SPPT PBB to be used as a standard in calculating BPHTB